Pete the cat and his magic sunglasses [book with audioplayer] - Dean, James, 1957-; Dean, Kim, 1969- (VOX Books, 2019)
In this hardcover picture book, Pete the Cat wakes up feeling grumpy-nothing seems to be going his way. But with the help of some magic sunglasses, Pete learns that a good mood has been inside him all along.